Du bleu au vert, quand l’île tente de tourner le dos à la mer - Christian Germanaz; Michel Sicre (VertigO)
While subscribing to the commonly recognized premice that the destination image is fundamental to ensure the visibility and perennity of a territory to be promoted as a tourist destination, the main focus of this paper is to analyze the different modes of introducing the vegetal landscape in destination images for use in tropical island spaces. Using examples of communications and development schemes that were implemented in the Seychelles, Mauritius and Reunion island this paper is an opportunity to reflect upon the interest and outcome of investing in "green" landscape for island economies which are heavily dependent on tourism. What mutually beneficial new perspectives can this indiano oceanic experience open in the caribbean and the guyanas?